Mucoromycosis and Wegner's Granulomatosis: A Case Report - Nasrin SHAYANFAR; Abbas ZAMANIAN; Elham BEHRANGI; Nahid KIANMEHR; Faezeh FIROUZI; Zahra AZIZIAN (Tehran University of Medical Sciences, 2018)
Wegener's granulomatosis is a rare vasculitis affecting the upper and lower respiratory tracts and kidneys. The cornerstone of treatment in these patients is immunosuppressive therapy, which may predispose the patient to super-infections such as fungal diseases per se. However, the fungal infection mimics the clinical manifestations of Wegener's diseases would lead to neglected course of the infection and subsequent morbidity and mortality especially if unusual organs are involved. Here we report a 21-yr-old female patient referred to a hospital, Tehran, Iran in 2013 with a neglected skin mucormycosis and the course of the disease and outcome with Wegener's granulomatosis.